AI-Driven Smart Education: Comparative Analysis of Digital Learning Readiness in Indonesia and Four Advanced Countries - Dirlam Dirlam; Iman Subasman; Ahmad Mujtahid; Ali Mumin Budiman; Umyati Umyati; Faat Nasyiruddin; Muhammad Azhar Muttaqin (Journal of Education Research, 2026)
The advancement of artificial intelligence (AI) has shifted educational paradigms from digitalization toward adaptive, data-driven, and learner-centered ecosystems. This study analyzes the readiness of AI-based digital learning systems in Indonesia, Australia, Finland, the United States, and Japan. A comparative qualitative multiple-case study design was employed, drawing on national policy documents, international organizational reports, and recent scholarly publications, analyzed through thematic content analysis and cross-case comparison. Five dimensions were examined: policy and regulatory frameworks, digital infrastructure, teacher competencies, student AI literacy, and ethical governance. Findings indicate that AI readiness is determined by the institutional integration of all five dimensions rather than technological advancement alone. Countries with stronger cross-dimensional alignment demonstrate higher readiness levels. Indonesia has advanced through national AI policies but faces persistent challenges in infrastructure equity, human resource capacity, and regulatory comprehensiveness. This study proposes an integrated conceptual framework to guide the development of inclusive, sustainable, and human-centered education policies.